The Influence of Accurate Software Proficiency and Digital Literacy on the Work Readiness of Accounting Students: The Moderating Role of Artificial Intelligence - Sa’Putra, Kiko; Sugeng, Sugeng (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
Digital transformation in accounting practice requires students to possess adequate technological competencies to enhance their competitiveness in the digital era. This study aims to analyze the impact of Accurate software proficiency and digital literacy on the employability of accounting students, as well as to examine the moderating role of artificial intelligence. A quantitative approach was employed, with primary data collected via an online questionnaire distributed to accounting students in Yogyakarta, East Java, and Central Java who are already using the Accurate software. The sampling method used was purposive sampling, with a total of 126 respondents. Data were analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) approach. The results indicate that proficiency in the Accurate software and digital literacy have a positive and significant influence on the work readiness of accounting students. These findings suggest that mastery of accounting applications and the ability to utilize digital technology constitute important forms of human capital in enhancing students’ professional readiness. However, artificial intelligence was not found to moderate the relationship between Accurate software proficiency or digital literacy and work readiness. Therefore, the competitiveness of accounting graduates is more directly influenced by technical competencies and digital literacy than by the use of artificial intelligence as a factor that strengthens the relationship between variables.